High-performance micro-nano composite material and preparation method thereof

By forming a porous structure of network-shaped silicon carbide fibers and nanozirconia in micro-nanoceramic materials, combined with titanium dioxide sol, the problem of insufficient material strength and toughness is solved, and high performance and stability is improved, and suitable for high impact environments.

CN119263862AActive Publication Date: 2025-01-07西安庄宸新材料工程技术研究院有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411611603.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-07
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Existing micro-nanoceramic materials have problems with insufficient material strength, toughness and structural uniformity in high performance and miniaturization applications, especially in extreme environments, which are difficult to meet structural strength and lightweight requirements.

Method used

By mixing the carbon source and the silicon source, adding pore-making agent to form a porous preform, and using microwave sintering technology to form a network-shaped silicon carbide fiber structure in a high temperature and high activity environment, combining nano zirconia and titanium dioxide sol to form a porous ceramic material. Improve the overall performance and stability of the material.

Benefits of technology

It significantly improves the strength, toughness and overall performance stability of the material, forms a continuous mesh structure to disperse stress, enhances the density and bonding strength of the ceramic matrix, and is suitable for high-impact environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005131034970000121
    Figure BDA0005131034970000121
  • Figure BDA0005131034970000131
    Figure BDA0005131034970000131
Patent Text Reader

Abstract

The invention discloses a high-performance micro-nano composite material and a preparation method thereof, and relates to the field of nano composite materials. The preparation method comprises the following steps: mixing a carbon source and a silicon source, adding a pore-forming agent to form a porous preform, and heating by using high-power microwaves to prepare the network-shaped silicon carbide fiber. The preparation method comprises the following steps: firstly, mixing and dissolving latticed silicon carbide fibers and silicon carbide powder to form a preform, using nano zirconium dioxide as a modified material, then adding titanium dioxide gel, enabling the titanium dioxide gel to enter pores, curing and crystallizing titanium dioxide during sintering, and meanwhile, forming a layer of titanium dioxide film in the sintering process, so that the titanium dioxide film is formed; the bonding strength is increased and the material performance is improved. According to the micro-nano porous composite ceramic prepared by the method, the network-shaped silicon carbide fiber is used as a framework, the silicon carbide powder, the nano zirconium oxide and the composite titanium dioxide are connected to form a double-layer ceramic structure, a carrier is high in strength and toughness and is in three-dimensional communication, and the internal structure is stable and the performance is excellent under high impact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, in particular to a high-performance micro-nano composite material. Background Art

[0002] Micro-nano materials refer to materials whose sizes are in the micron and nanometer range. In terms of size range, it is between macroscopic materials and microscopic particles such as atoms and molecules. This special scale gives micro-nano materials a series of unique properties. In terms of performance, micro-nano materials have a small size effect. When the size of a material is reduced to the micro-nano scale, its physical and chemical properties will change significantly. For example, the melting point, magnetic properties, and optical properties of the material are different from those of bulk materials. The quantum size effect is also prominent. The energy level of electrons is no longer continuous at the micro-nano scale, but discrete, which affects the electrical, optical and other properties of the material. In addition, micro-nano materials also exhibit high specific surface area and surface effects. The ratio of the number of surface atoms to the total number of atoms increases significantly, which enhances the surface activity of the material, and makes the adsorption and catalytic effects on the surrounding environment more significant. At the same time, they also have special mechanical properties that macroscopic materials do not have.

[0003] As an important type of micro-nano materials, micro-nano ceramics have important application significance. In the field of electronics, micro-nano ceramics can be used to manufacture high-performance electronic components, such as ceramic capacitors, varistors, etc. Its precisely controlled micro-nano structure can improve the capacitance, withstand voltage and other properties of the components, solving the problems of traditional electronic ceramic components in the process of miniaturization and high performance, and enabling electronic equipment to develop in a smaller and more efficient direction. In the field of biomedicine, the good biocompatibility of micro-nano ceramics enables them to be used in the preparation of implant materials, drug carriers, etc. For example, as a drug carrier, the high specific surface area of ​​micro-nano ceramics can load a large amount of drugs, and can achieve targeted release of drugs through surface modification, effectively solving the problem of precise drug delivery in the body, reducing side effects on normal tissues, and improving the treatment effect. In the field of energy, micro-nano ceramics can be used in fuel cells, lithium-ion batteries, etc. In fuel cells, their special microstructure and properties help to improve the catalytic activity and ion conductivity of the electrode, solving the problem of energy conversion efficiency and stability of fuel cells; in lithium-ion batteries, they can improve the charge and discharge performance and cycle life of electrode materials. In the aerospace field, the high strength, high temperature resistance, and low density of micro-nano ceramics can be used to manufacture thermal insulation materials, structural components, etc. for aircraft, solving the problem of materials having to ensure both structural strength and lightweight requirements in extreme environments, thereby improving the performance and reliability of aircraft.

[0004] In short, micro-nano materials, especially micro-nano ceramics, have shown great application potential in many fields with their unique properties, providing new material approaches for solving key technical problems in various fields and playing an important role in promoting the development of modern science and technology. Summary of the invention

[0005] The purpose of the present invention is to provide a high-performance micro-nano composite material to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-performance micro-nano composite material and a preparation method thereof, characterized in that it comprises the following preparation steps:

[0007] (1) mixing a carbon source and a silicon source according to a volume ratio, adding a pore-forming agent and a binder, mixing and rolling, and obtaining a precursor;

[0008] (2) placing the precursor into a microwave sintering furnace, adjusting parameters, and sintering to obtain a network-like silicon carbide fiber;

[0009] (3) Take pseudo-boehmite, add deionized water to dissolve, stir to form a uniform slurry, continue to add potassium citrate, stir evenly and let stand;

[0010] (4) continuing to add the phosphate mixture or phosphoric acid to the mixed slurry of step (5), stirring sufficiently, and obtaining aluminum phosphate sol after the reaction is complete;

[0011] (5) dispersing the network-like silicon carbide fibers in deionized water, adding micro silicon carbide particles, nano zirconium oxide powder, aluminum phosphate sol and a dispersant, and stirring evenly to obtain a sintered preform;

[0012] (6) placing the sintered preform in a reaction furnace for sintering to obtain nano zirconium dioxide modified micro-nano porous silicon carbide ceramics;

[0013] (7) Take tetra-n-butyl titanate, slowly add it dropwise into anhydrous ethanol under stirring, and stir evenly to obtain solution A;

[0014] (8) dissolving anhydrous ethanol in deionized water, and adding dropwise to concentrated hydrochloric acid to adjust the pH value to obtain solution B;

[0015] (9) adding solution B dropwise into solution A and stirring evenly to obtain a titanium dioxide sol;

[0016] (10) immersing the nano zirconium dioxide modified micro-nano porous silicon carbide ceramic obtained in step (6) in a titanium dioxide sol, taking it out and drying it, and repeating the process several times to obtain a titanium dioxide sol modified ceramic;

[0017] (11) The titanium dioxide sol-modified ceramic is placed in a reaction furnace for sintering. After the reaction is complete, the ceramic is molded and cooled to obtain a high-performance micro-nano composite material, namely, nano-zirconium dioxide-modified micro-nano porous silicon carbide / titanium dioxide composite ceramic.

[0018] The nano zirconium oxide is prepared by the following method:

[0019] (i) mixing zirconium salt, tartaric acid and ammonium nitrate to obtain a solution;

[0020] (ii) titrating the mixed solution obtained in step (1) with aqueous ammonia to produce a precipitation reaction to obtain Zr(OH)4 colloid;

[0021] (iii) aging, water washing and alcohol washing the Zr(OH)4 colloid in sequence to obtain a hydrated zirconium gel, and drying to obtain a zirconium precursor; and calcining the obtained zirconium precursor to obtain nano zirconium oxide.

[0022] Furthermore, in step (1), the carbon source is carbon powder, the silicon source is quartz sand, the molar ratio thereof is 1 to 10:1, the pore-forming agent is polymethyl methacrylate microspheres; and the binder is a polyethylene glycol aqueous solution.

[0023] Furthermore, the power input rate of step (2) is 0.1-0.5 kW / min; the sintering temperature is 900-1500° C., and the sintering time is 0.5-1 h.

[0024] Furthermore, the particle size of the micro silicon carbide particles in step (5) is 5 to 10 μm; the mass ratio of the network silicon carbide fibers, micro silicon carbide particles, nano zirconium oxide powder and aluminum phosphate sol is 5 to 10:25 to 35:5 to 10:20 to 30.

[0025] Furthermore, the sintering process in step (6) is 150-200°C for 1-2h, then heated to 300-400°C for 2-4h, and then heated to 1150-1250°C for 1-2h.

[0026] Furthermore, the mass percentage of concentrated hydrochloric acid in step (8) is 25-35%; and the pH value of the titration is 2-3.

[0027] Furthermore, the sintering temperature in step (11) is 1150-1250° C. and the sintering time is 2-4 hours.

[0028] Furthermore, a high-performance micro-nano composite material is provided, characterized in that the material is prepared by the preparation method.

[0029] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0030] The present invention mixes a carbon source and a silicon source, adds a pore-forming agent to form a porous preform, and then uses microwave heating. Under the limitation of a specific power range and input power rate, gas molecules are ionized to form plasma, and the plasma enters the pores in a three-dimensional multi-directional form. Silicon atoms and carbon atoms combine to form silicon carbide under the high temperature and high activity environment of the plasma. Due to the multi-directional distribution of the plasma in the pores, the silicon carbide continues to grow and connect with each other, and finally forms a network-like silicon carbide fiber structure. This three-dimensional reaction mode can make the fiber grow uniformly in the entire space of the porous precursor to form a continuous network, and obtain a network-like silicon carbide fiber, which can form a "skeleton"-like support structure in the ceramic matrix, effectively disperse stress, and prevent crack expansion, thereby significantly improving the strength and toughness of the silicon carbide ceramic; the grid-like silicon carbide fiber can be better combined with the ceramic matrix during the preparation process, inhibiting the growth of ceramic crystals, making the microstructure of the ceramic material more uniform, improving the overall performance stability of the material, and reducing the performance differences and defects caused by uneven microstructure. The present invention allows the precursor to be heated evenly by limiting the power rate to form a uniform network fiber structure. At a slower heating rate, the chemical reaction in the precursor can proceed more fully, thereby improving the overall quality and performance of the fiber. After reaching the sintering temperature through microwave input, the appropriate insulation time is controlled to ensure that the crystals grow completely and have uniform size, which is beneficial to the relaxation of the internal pressure of the network fiber and a more stable structure.

[0031] The present invention uses nano zirconium oxide to modify micro-nano composite porous ceramics. After the nano zirconium oxide is added to the porous ceramic system, it can fill the pores and structural gaps formed by silicon carbide fibers and silicon carbide powder, play a reinforcing role, and improve the overall hardness of the porous ceramics. The nano zirconium oxide has certain activity at high temperatures, can reduce the sintering temperature, promote the sintering process between the silicon carbide fibers and the silicon carbide powder, and make the structure of the material more compact. At the same time, nano particles are adsorbed on the surfaces of the silicon carbide fibers and the silicon carbide powder, reducing the agglomeration phenomenon between them, making the microstructure of the material more uniform, and is conducive to improving the integrity of the material.

[0032] The present invention first uses grid-like silicon carbide fibers, silicon carbide powder, and nano-zirconium oxide to mix and dissolve to form a preform, and then adds titanium dioxide sol gel. The titanium dioxide sol can penetrate into the pores of the preform. In the subsequent sintering process, the titanium dioxide will solidify and crystallize, forming chemical bonds or physical bonds with the network-like silicon carbide fibers and silicon carbide particles, thereby enhancing the structural strength of the preform and making the composite porous ceramic more dense and stable. At the same time, a layer of titanium dioxide film is formed during the sintering process to increase the bonding strength and improve the material performance.

[0033] The micro-nano porous composite ceramic prepared by the present invention uses network-like silicon carbide fiber as the skeleton, connects silicon carbide powder and nano zirconium oxide, and composites titanium dioxide to form a double-layer ceramic structure. The carrier has high strength, strong toughness, and three-dimensional connectivity. Under high impact, the internal structure is stable and the performance is excellent. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the high-performance micro-nano composite materials prepared in the following examples are as follows:

[0036] Porosity: GB / T 3810.3-2016

[0037] Pore ​​size: GB / T 1967-1996

[0038] Thermal conductivity: GB / T 39862-2021

[0039] Compressive strength: GB / T 1964-1996

[0040] Vickers hardness: GB / T 4340.1-2009

[0041] Example 1

[0042] (1) 40 parts of carbon powder and 10 parts of quartz sand powder were mixed evenly, 5 parts of polymethyl methacrylate microspheres and 10 parts of polyethylene glycol aqueous solution were added, and the mixture was mixed and rolled to obtain a precursor;

[0043] (2) placing the precursor into a microwave sintering furnace at a power input rate of 0.3 kW / min, 1200°C, and 45 min to obtain a network-like silicon carbide fiber;

[0044] (3) Take 20 parts of boehmite, add deionized water to dissolve, stir to form a uniform slurry, continue to add 15 parts of potassium citrate, stir evenly and let stand for 12 hours;

[0045] (4) adding phosphoric acid having a mass concentration of 85% to the mixed slurry of step (3), stirring the mixture sufficiently, and obtaining aluminum phosphate sol after the reaction is complete;

[0046] (5) 25 parts of ZrCl4, 2 parts of tartaric acid, and 20 parts of ammonium chloride with a concentration of 6.6 mol / L were mixed to obtain a mixed solution;

[0047] (6) adding 80 parts by mass of 35% ammonia water dropwise to the mixed solution obtained in step (7) to carry out a precipitation reaction to obtain Zr(OH)4 colloid;

[0048] (7) Aging and washing the Zr(OH)4 colloid to obtain a hydrated zirconium gel, and drying to obtain a zirconium precursor; calcining the obtained zirconium precursor at 800°C for 2h to obtain nano zirconium oxide.

[0049] (8) dispersing 8 parts of network-like silicon carbide fibers in deionized water, adding 30 parts of micro silicon carbide particles, 5 parts of nano zirconium oxide powder, 20 parts of aluminum phosphate sol and 10 parts of polyethylene glycol, and stirring evenly to obtain a sintered preform;

[0050] (9) placing the sintered preform in a reaction furnace at 175° C. for 1.5 h, then heating to 350° C. for 3 h, then heating to 1200° C. for 1.5 h, and sintering to obtain nano-zirconium dioxide modified micro-nano porous silicon carbide ceramics;

[0051] (10) Take 20 parts of tetra-n-butyl titanate, slowly add it dropwise into anhydrous ethanol under stirring, and stir evenly to obtain solution A;

[0052] (11) dissolving anhydrous ethanol in deionized water, and adding dropwise to 30% concentrated hydrochloric acid to adjust the pH value to 2.5 to obtain solution B;

[0053] (12) adding solution B dropwise into solution A and stirring evenly to obtain a titanium dioxide sol;

[0054] (13) immersing the nano zirconium dioxide modified micro-nano porous silicon carbide ceramic obtained in step (9) in a titanium dioxide sol, taking it out and drying it, and repeating the process multiple times to obtain a titanium dioxide sol modified ceramic;

[0055] (14) The titanium dioxide sol-modified ceramics are placed in a reaction furnace and sintered at 1200°C for 3 hours. After the reaction is complete, the ceramics are molded and cooled to obtain a high-performance micro-nano composite material, namely, nano-zirconium dioxide-modified micro-nano porous silicon carbide / titanium dioxide composite ceramics.

[0056] Example 2

[0057] (1) 50 parts of carbon powder and 15 parts of quartz sand powder were mixed evenly, 10 parts of polymethyl methacrylate microspheres and 15 parts of polyethylene glycol aqueous solution were added, and the mixture was mixed and rolled to obtain a precursor;

[0058] (2) placing the precursor into a microwave sintering furnace, with a power input rate of 0.5 kW / min, 1500°C, and 60 min, and sintering to obtain a network-like silicon carbide fiber;

[0059] (3) Take 30 parts of boehmite, add deionized water to dissolve, stir to form a uniform slurry, continue to add 20 parts of potassium citrate, stir evenly and let stand for 17 hours;

[0060] (4) adding phosphoric acid having a mass concentration of 90% to the mixed slurry of step (3), stirring the mixture sufficiently, and obtaining aluminum phosphate sol after the reaction is complete;

[0061] (5) 30 parts of ZrCl4, 3 parts of tartaric acid, and 25 parts of 7.0 mol / L ammonium chloride were mixed to obtain a mixed solution;

[0062] (6) adding 100 parts by mass of 40% ammonia water dropwise to the mixed solution obtained in step (5) to carry out a precipitation reaction to obtain Zr(OH)4 colloid;

[0063] (7) Aging and washing the Zr(OH)4 colloid to obtain a hydrated zirconium gel, and drying to obtain a zirconium precursor; calcining the obtained zirconium precursor at 1000°C for 3h to obtain nano zirconium oxide.

[0064] (8) dispersing 10 parts of network-like silicon carbide fibers in deionized water, adding 35 parts of micro silicon carbide particles, 10 parts of nano zirconium oxide powder, 30 parts of aluminum phosphate sol and 15 parts of polyethylene glycol, and stirring evenly to obtain a sintered preform;

[0065] (9) placing the sintered preform in a reaction furnace at 200° C. for 2 h, then heating to 400° C. for 4 h, then heating to 1250° C. for 2 h, sintering to obtain nano-zirconium dioxide modified micro-nano porous silicon carbide ceramics;

[0066] (10) Take 25 parts of tetra-n-butyl titanate, slowly add it dropwise into anhydrous ethanol under stirring, and stir evenly to obtain solution A;

[0067] (11) dissolving anhydrous ethanol in deionized water, and adding dropwise to 30% concentrated hydrochloric acid to adjust the pH value to 3 to obtain solution B;

[0068] (12) adding solution B dropwise into solution A and stirring evenly to obtain a titanium dioxide sol;

[0069] (13) immersing the nano zirconium dioxide modified micro-nano porous silicon carbide ceramic obtained in step (9) in a titanium dioxide sol, taking it out and drying it, and repeating the process multiple times to obtain a titanium dioxide sol modified ceramic;

[0070] (14) The titanium dioxide sol-modified ceramics are placed in a reaction furnace and sintered at 1250°C for 4 hours. After the reaction is complete, the ceramics are molded and cooled to obtain a high-performance micro-nano composite material, namely, nano-zirconium dioxide-modified micro-nano porous silicon carbide / titanium dioxide composite ceramics.

[0071] Example 3

[0072] (1) 30 parts of carbon powder and 5 parts of quartz sand powder were mixed evenly, 5 parts of polymethyl methacrylate microspheres and 5 parts of polyethylene glycol aqueous solution were added, and the mixture was mixed and rolled to obtain a precursor;

[0073] (2) placing the precursor into a microwave sintering furnace, with a power input rate of 0.1 kW / min, 900°C, and 30 min, and sintering to obtain a network-like silicon carbide fiber;

[0074] (3) Take 10 parts of boehmite, add deionized water to dissolve, stir to form a uniform slurry, continue to add 10 parts of potassium citrate, stir evenly and let stand for 8 hours;

[0075] (4) adding phosphoric acid having a mass concentration of 80% to the mixed slurry of step (3), stirring sufficiently, and obtaining aluminum phosphate sol after the reaction is complete;

[0076] (5) 20 parts of ZrCl4, 1 part of tartaric acid, and 15 parts of 6.0 mol / L ammonium chloride were mixed to obtain a mixed solution;

[0077] (6) adding 60 parts by mass of 30% ammonia water dropwise to the mixed solution obtained in step (5) to carry out a precipitation reaction to obtain Zr(OH)4 colloid;

[0078] (7) Aging and washing the Zr(OH)4 colloid to obtain a hydrated zirconium gel, and drying to obtain a zirconium precursor; calcining the obtained zirconium precursor at 650°C for 1 hour to obtain nano zirconium oxide.

[0079] (8) dispersing 5 parts of network-like silicon carbide fibers in deionized water, adding 25 parts of micro silicon carbide particles, 5 parts of nano zirconium oxide powder, 20 parts of aluminum phosphate sol and 5 parts of polyethylene glycol, and stirring evenly to obtain a sintered preform;

[0080] (9) placing the sintered preform in a reaction furnace at 100° C. for 1 hour, then heating to 300° C. for 2 hours, and then heating to 1150° C. for 1 hour, sintering to obtain nano-zirconium dioxide modified micro-nano porous silicon carbide ceramics;

[0081] (10) Take 15 parts of tetra-n-butyl titanate, slowly add it dropwise into anhydrous ethanol under stirring, and stir evenly to obtain solution A;

[0082] (11) dissolving anhydrous ethanol in deionized water, and adding dropwise to 30% concentrated hydrochloric acid to adjust the pH value to 2.0 to obtain solution B;

[0083] (12) adding solution B dropwise into solution A and stirring evenly to obtain a titanium dioxide sol;

[0084] (13) immersing the nano zirconium dioxide modified micro-nano porous silicon carbide ceramic obtained in step (9) in a titanium dioxide sol, taking it out and drying it, and repeating the process multiple times to obtain a titanium dioxide sol modified ceramic;

[0085] (14) The titanium dioxide sol-modified ceramics are placed in a reaction furnace and sintered at 1150°C for 2 hours. After the reaction is complete, the ceramics are molded and cooled to obtain a high-performance micro-nano composite material, namely, nano-zirconium dioxide-modified micro-nano porous silicon carbide / titanium dioxide composite ceramics.

[0086] Comparative Example 1

[0087] The difference between Comparative Example 1 and Example 1 is that steps (1) and (2) are deleted, and step (8) is changed to disperse 8 parts of commercially available nano silicon carbide fibers in deionized water, add 30 parts of micro silicon carbide particles, 5 parts of nano zirconium oxide powder, 20 parts of aluminum phosphate sol and 10 parts of polyethylene glycol, and stir evenly to obtain a sintered preform; the remaining steps are the same as in Example 1.

[0088] Comparative Example 2

[0089] The difference between Comparative Example 2 and Example 1 is that steps (1) and (2) are deleted, and step (8) is changed to disperse 8 parts of commercially available nano-silicon dioxide fibers in deionized water, add 30 parts of micro silicon carbide particles, 5 parts of nano-zirconium oxide powder, 20 parts of aluminum phosphate sol and 10 parts of polyethylene glycol, and stir evenly to obtain a sintered preform; the remaining steps are the same as those in Example 1.

[0090] Comparative Example 3

[0091] The difference between Comparative Example 3 and Example 1 is that steps (1) and (2) are deleted, and step (8) is changed to disperse 8 parts of commercially available nano-alumina fibers in deionized water, add 30 parts of micro silicon carbide particles, 5 parts of nano-zirconium oxide powder, 20 parts of aluminum phosphate sol and 10 parts of polyethylene glycol, and stir evenly to obtain a sintered preform; the remaining steps are the same as Example 1.

[0092] Comparative Example 4

[0093] The difference between Comparative Example 4 and Example 1 is that steps (5) to (7) are deleted, 8 parts of network silicon carbide fibers are dispersed in deionized water, 30 parts of micro silicon carbide particles, 20 parts of aluminum phosphate sol and 10 parts of polyethylene glycol are added and stirred evenly to obtain a sintered preform; the remaining steps are the same as in Example 1.

[0094] Comparative Example 5

[0095] The difference between Comparative Example 5 and Example 1 is that steps (5) to (7) are deleted, 8 parts of network silicon carbide fibers are dispersed in deionized water, 30 parts of micro silicon carbide particles, 5 parts of commercially available nano zirconium oxide, 20 parts of aluminum phosphate sol and 10 parts of polyethylene glycol are added and stirred evenly to obtain a sintered preform; the remaining steps are the same as in Example 1.

[0096] Comparative Example 6

[0097] The difference between Comparative Example 6 and Example 1 is that steps (10) to (14) are deleted, and step (9) is changed to sintering the preform in a reactor at 175°C for 1.5 hours, then heating to 350°C for 3 hours, and then heating to 1200°C for 1.5 hours, and sintering to obtain a high-performance micro-nano composite material, namely, nano-zirconium dioxide modified micro-nano porous silicon carbide ceramics; the remaining steps are the same as in Example 1.

[0098] Comparative Example 7

[0099] The difference between Comparative Example 7 and Example 1 is that steps (10) to (12) are deleted, and step (13) is changed to immersing the nano zirconium dioxide modified micro-nano porous silicon carbide ceramic obtained in step (9) in a commercially available alumina solution, taking it out and drying it, and repeating the process multiple times to obtain titanium dioxide sol modified ceramic; the remaining steps are the same as Example 1.

[0100] Comparative Example 8

[0101] The difference between Comparative Example 8 and Example 1 is step (2). Step (2) is changed to placing the precursor into a microwave sintering furnace with a power input rate of 0.05 kW / min, 1200°C, and 45 min, and sintering to obtain silicon carbide fiber; the remaining steps are the same as Example 1.

[0102] Comparative Example 9

[0103] The difference between Comparative Example 9 and Example 1 is step (2). Step (2) is changed to placing the precursor into a microwave sintering furnace with a power input rate of 0.6 kW / min, 1200°C, and 45 min, and sintering to obtain silicon carbide fiber; the remaining steps are the same as Example 1.

[0104] Comparative Example 10

[0105] The difference between Comparative Example 10 and Example 1 is step (2). Step (2) is changed to placing the precursor into a vacuum sintering furnace at a pressure of 25 MPa, 1200°C, and 45 min to sinter and form silicon carbide fibers. The remaining steps are the same as in Example 1.

[0106] Effect example

[0107] Table 1 below shows the performance analysis results of the high-performance micro-nano composite materials of Examples 1 to 3 and Comparative Examples 1 to 7 of the present invention.

[0108] Table 1

[0109]

[0110]

[0111] From the data comparison of the embodiment and the comparative example, it can be found that the present invention first mixes the carbon source and the silicon source, adds the pore-forming agent to form a porous preform, and then uses high-power microwave heating. Under the action of high-power microwaves, the gas molecules will be ionized to form plasma, and these plasmas enter the pores in a three-dimensional multi-directional form. Silicon atoms and carbon atoms combine to form silicon carbide under the high temperature and high activity environment of the plasma. Due to the multi-directional distribution of the plasma in the pores, silicon carbide continues to grow and connect to each other, and finally forms a network-like silicon carbide fiber structure. This three-dimensional reaction mode can make the fiber grow uniformly in the entire space of the porous precursor, forming a continuous net, and preparing a network-like silicon carbide fiber. The present invention allows the precursor to be heated uniformly by limiting the power rate, forming a uniform network-like fiber structure. At a slower rate of increase, the chemical reaction in the precursor can be carried out more fully, improving the overall quality and performance of the fiber, and then after reaching the sintering temperature through microwave input, the appropriate insulation time is controlled, so that the crystal grows completely and the size is uniform, which is conducive to the relaxation of the internal pressure of the network-like fiber and the structure is more stable. The present invention first uses grid-like silicon carbide fiber, silicon carbide powder, and mixed dissolution to form a preform, uses nano zirconium dioxide as a modified material, and then adds titanium dioxide gel, which enters the pores. During sintering, titanium dioxide solidifies and crystallizes, and a layer of titanium dioxide film is formed during the sintering process, which increases the bonding strength and improves the material performance. The micro-nano porous composite ceramic prepared by the present invention uses network-like silicon carbide fiber as a skeleton, connects silicon carbide powder and nano zirconium oxide, and composites titanium dioxide to form a double-layer ceramic structure. The carrier has high strength, strong toughness, and three-dimensional connectivity. Under high impact, the internal structure is stable and the performance is excellent.

[0112] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and no mark in the claims should be regarded as limiting the claims involved.

Claims

1. A method for preparing a high-performance micro-nano composite material, characterized in that: The method comprises the following preparation steps: (1) mixing a carbon source and a silicon source according to a volume ratio, adding a pore-forming agent and a binder, mixing and rolling, and obtaining a precursor; (2) placing the precursor into a microwave sintering furnace, adjusting parameters, and sintering to obtain a network-like silicon carbide fiber; (3) Take pseudo-boehmite, add deionized water to dissolve, stir to form a uniform slurry, continue to add potassium citrate, stir evenly and let stand; (4) continuing to add the phosphate mixture or phosphoric acid to the mixed slurry of step (5), stirring sufficiently, and obtaining aluminum phosphate sol after the reaction is complete; (5) dispersing the network-like silicon carbide fibers in deionized water, adding micro silicon carbide particles, nano zirconium oxide powder, aluminum phosphate sol and a dispersant, and stirring evenly to obtain a sintered preform; (6) placing the sintered preform in a reaction furnace for sintering to obtain nano zirconium dioxide modified micro-nano porous silicon carbide ceramics; (7) Take tetra-n-butyl titanate, slowly add it dropwise into anhydrous ethanol under stirring, and stir evenly to obtain solution A; (8) dissolving anhydrous ethanol in deionized water, and adding dropwise to concentrated hydrochloric acid to adjust the pH value to obtain solution B; (9) adding solution B dropwise into solution A and stirring evenly to obtain a titanium dioxide sol; (10) immersing the nano zirconium dioxide modified micro-nano porous silicon carbide ceramic obtained in step (6) in a titanium dioxide sol, taking it out and drying it, and repeating the process several times to obtain a titanium dioxide sol modified ceramic; (11) The titanium dioxide sol modified ceramic is placed in a reaction furnace for sintering, and the reaction is complete, and the molding and cooling are performed to obtain a high-performance micro-nano composite material, namely, nano zirconium dioxide modified micro-nano porous silicon carbide / titanium dioxide composite ceramic; The nano zirconium oxide is prepared by the following method: (i) mixing zirconium salt, tartaric acid and ammonium nitrate to obtain a solution; (ii) titrating the mixed solution obtained in step (1) with aqueous ammonia to produce a precipitation reaction to obtain Zr(OH)4 colloid; (iii) aging, water washing and alcohol washing the Zr(OH)4 colloid in sequence to obtain a hydrated zirconium gel, and drying to obtain a zirconium precursor; and calcining the obtained zirconium precursor to obtain nano zirconium oxide.

2. The method for preparing a high-performance micro-nano composite material according to claim 1, characterized in that: In the step (1), the carbon source is carbon powder, the silicon source is quartz sand powder, the molar ratio thereof is 1 to 10:1, the pore-forming agent is polymethyl methacrylate microspheres; and the binder is polyethylene glycol aqueous solution.

3. The method for preparing a high-performance micro-nano composite material according to claim 1, characterized in that: The power input rate of the step (2) is 0.1-0.5 kW / min; the sintering temperature is 900-1500° C., and the sintering time is 0.5-1 h.

4. The method for preparing a high-performance micro-nano composite material according to claim 1, characterized in that: The particle size of the micro silicon carbide particles in step (5) is 5 to 10 μm; the mass ratio of the network silicon carbide fibers, micro silicon carbide particles, nano zirconium oxide powder and aluminum phosphate sol is 5 to 10:25 to 35:5 to 10:20 to 30.

5. The method for preparing a high-performance micro-nano composite material according to claim 1, characterized in that: The sintering process of step (6) is 150-200°C for 1-2h, then heated to 300-400°C for 2-4h, and then heated to 1150-1250°C for 1-2h.

6. The method for preparing a high-performance micro-nano composite material according to claim 1, characterized in that: The mass percentage of concentrated hydrochloric acid in step (8) is 25-35%; the pH value of the titration is 2-3.

7. The method for preparing a high-performance micro-nano composite material according to claim 1, characterized in that: The sintering temperature in step (11) is 1150-1250° C. and the sintering time is 2-4 hours.

8. A high-performance micro-nano composite material, characterized in that: The material is prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Three-dimensional silicon carbide fiber-reinforced silicon dioxide-zirconium dioxide multiphase ceramic composite material and preparation method thereof

    CN108147796A

  • Silicon carbide fiber reinforced ceramic based structure wave absorption composite material and preparation method thereof

    CN108191446A

  • Preparation method of silicon carbide fiber reinforced silicon carbide composite material

    CN111606715A

  • Silicon carbide ceramic fiber and method for producing the same

    JP2004277890A

  • An improved process for producing silica aerogel thermal insulation product with increased efficiency.

    WO2017009858A1